KNOWLEDGE OF WARNING SIGNS OF HYPERTENSION CRISIS AND EMERGENCY HELP SEEKING BEHAVIOR AMONG PRODUCTIVE AGE ADULTS - Nurul Imam; Budi Artini; Khalifatus Zuhriyah Alfianti; Martha Lowrani Siagian (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2026)
Background: Hypertensive crisis is an emergency condition that has the potential to cause damage to target organs and death if not treated quickly and appropriately. The low level of knowledge of the productive age community about the danger signs of a hypertension crisis can contribute to delays in seeking emergency medical attention. Purpose of this study is to determine the level of knowledge of productive age regarding the danger signs of a hypertensive crisis and emergency medical assistance seeking behavior. Methods: This study used a quantitative design with a cross-sectional approach conducted in Kelurahan Pakis, Sawahan, Surabaya, with a sample of 196 respondents selected using a simple random sampling technique. Data was collected using a structured questionnaire that has been tested for validity and reliability. Data analysis was carried out univariate and bivariate using the Chi-square test with a significance level of p < 0.05. Results: The results showed that most of the respondents had a good level of knowledge (36.7%), followed by the categories of sufficient (34.7%) and insufficient (28.6%). Emergency medical assistance seeking behavior was classified as good in 53.1% of respondents, but there were still 46.9% with inappropriate behavior. The results of the bivariate analysis showed a significant relationship between knowledge level and emergency medical assistance seeking behavior (p = 0.001). These findings show that knowledge level has an important role in shaping medical attention seeking behavior in hypertensive emergency conditions. Conclusion: Comprehensive interventions are expected to lower the risk of treatment delays and more severe complications.